Economic benefit, convenience dan risk benefit dalam mempengaruhi penggunaan Fintech yang berulang - Fani Firmansyah; Choirul Rozi; Maretha Ika Prajawati (Jurnal Ekonomi Modernisasi, 2021)
Almost all activities in all sectors are supported by technology and information. Fintech has attracted much attention, but the current use of Fintech is still in doubt. This study aims specifically to determine the specific benefits that are felt as well as the negative impacts arising from the use of Fintech together can influence the use of Fintech repeatedly, specifically for the younger generation. This type of research is quantitative research. The sampling method used is Quota Sampling. In this study, 20 samples will be taken from several universities in Malang. Based on the results of the research and discussion of this study, it can be concluded that the higher the economic benefits and comfort provided by Fintech, the higher the recurring assistance for Fintech. Financial risk (financial influence) as a moderating variable that influences the effect of economic benefits (economic benefits) on the continuation of financial technology intentions (intention to use repeatedly in financial technology products). The financial risk offered by Fintech means the higher interest in using Fintech because of the higher the level of Fintech usage the higher.